(untitled) (Texas Journal of Philology, Culture and History, 2026)
The article examines pragmatic literary theory as a new phenomenon emerging in opposition to traditional literary studies. It identifies the factors that have contributed to the emergence of this theory, outlines its analytical “instruments,” core principles, and practical approaches to the analysis of literary works, and also considers the views of several critics of the new theoretical paradigm